2015
DOI: 10.5194/acp-15-3445-2015
|View full text |Cite
|
Sign up to set email alerts
|

Long-term particulate matter modeling for health effect studies in California – Part 1: Model performance on temporal and spatial variations

Abstract: Abstract. For the first time, a ∼ decadal (9 years from 2000 to 2008) air quality model simulation with 4 km horizontal resolution over populated regions and daily time resolution has been conducted for California to provide air quality data for health effect studies. Model predictions are compared to measurements to evaluate the accuracy of the simulation with an emphasis on spatial and temporal variations that could be used in epidemiology studies. Better model performance is found at longer averaging times,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 107 publications
3
69
0
Order By: Relevance
“…A previous study has revealed that air pollution levels are associated with these parameters in highly polluted regions in China (Y. . It is also demonstrated that bias in predicted meteorological parameters by WRF contributes to bias in PM 2.5 prediction (Hu et al, 2015c;Zhang et al, 2014a, b). A companion study is undergoing to evaluate the sensitivity of predictions to meteorological fields.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has revealed that air pollution levels are associated with these parameters in highly polluted regions in China (Y. . It is also demonstrated that bias in predicted meteorological parameters by WRF contributes to bias in PM 2.5 prediction (Hu et al, 2015c;Zhang et al, 2014a, b). A companion study is undergoing to evaluate the sensitivity of predictions to meteorological fields.…”
Section: Discussionmentioning
confidence: 99%
“…Air quality was simulated using the UCD-CIT (University of California, Davis -California Institute of Technology) 3-D regional chemical transport model (Kleeman and Cass, 2001;Ying et al, 2007;Hu et al, 2015). The SAPRC11 chemical mechanism was used to represent gas-phase chemical reactions.…”
Section: Regional Chemical Transport Model Configuration and Simulationmentioning
confidence: 99%
“…Performance of the ensemble predictions at the city was calculated using the withheld observations to evaluate the performance. The evaluation process was repeated for each of the 60 cities and the performance was compared to that with individual inventories (shown in Table S3 Hu et al, 2014bHu et al, , 2015b. Ensemble predictions were also calculated with daily and monthly averages for PM 2.5 , in addition to the calculation with annual averages discussed above.…”
Section: Ensemble Predictionsmentioning
confidence: 99%